The nature of the cognitive advantage: A quarter of a century later - Karlinsky, A.; Lohse, K. R.; Hodges, N. J. (International Journal of Sport Psychology, 2015)
Sport expertise research has flourished within the last quarter of a century, since the publication by Starkes (1987) on the nature of the cognitive advantage in field hockey. In this review article we consider and evaluate how this early research has influenced current paradigms used to study expertise and how conclusions and theories have developed and changed over the past 25 years. In order to provide a framework for selection of studies we focused on studies most related to memory and cognition and inclusion of the original tasks used by Starkes (1987); that is, recall, recognition and decision-making. We consider how more recent tools, typically related to brain processes, impact our understanding of the role of cognition in the expert advantage in sport and more specifically the interrelationships between motor and perceptual-cognitive skills. We end with a summary of some key quotes from the 1987 paper and consider the relevance of these quotes against the backdrop of the reviewed literature.